A New Version of Prakaamy Distribution with Properties and Applications - Saraja, D. Vedavathi; Subramanian, C.; Rao, N. Srinivasa (International Journal of Membrane Science and Technology, 2023)
This paper introduces a novel statistical model, the Length-Biased version of the Prakaamy distribution, characterized by one parameter. The study presents a comprehensive analysis of this distribution, including the derivation of its probability density function (PDF), cumulative distribution function (CDF), moments, moment generating function, characteristics function, reliability analysis, ordered statistics, maximum likelihood estimation of parameter, entropies, likelihood ratio test, and Bonferroni and Lorenz curves. To validate the effectiveness of the proposed model, it is applied to two real-life time data sets, demonstrating its applicability and utility in practical scenarios.